1980
DOI: 10.1063/1.440483
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric quenching of vibrationally excited O2(1Δ)

Abstract: Flash photolysis of O3 in the Hartley band has been coupled with absorption spectroscopic detection of O2(1Δ, v=0) and resonance fluorescence detection of O(3P) to analyze the fate of O2(1Δ, v?1) in an atmospheric environment. The results indicate a rapid vibrational deactivation under atmospheric conditions. The same analysis permits an estimate of the relative quantum yield of O2(1Δ, v?1) in the photolysis. Similarly, an upper limit for the channel of the O(1D)+O3 reaction yielding O2(1Σ) is derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Collins and Husain 14 found the v = 1 levels of a 1 Δ g and of the ground-state X 3 Σ g − are strongly coupled, such that the reaction to produce O 2 (X 3 Σ g − , v = 1) and O 2 (a 1 Δ g , v = 0) and its reverse are very fast. Klais et al 15 concluded from their experiments that O 2 (a 1 Δ g , v = 1) removal in O 2 did not lead to enhanced production of O 2 (a 1 Δ g , v = 0), a significantly different conclusion than that of the earlier study. We will show the results of Collins and Husain are consistent with the more direct experimental data presented here.…”
Section: ■ Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Collins and Husain 14 found the v = 1 levels of a 1 Δ g and of the ground-state X 3 Σ g − are strongly coupled, such that the reaction to produce O 2 (X 3 Σ g − , v = 1) and O 2 (a 1 Δ g , v = 0) and its reverse are very fast. Klais et al 15 concluded from their experiments that O 2 (a 1 Δ g , v = 1) removal in O 2 did not lead to enhanced production of O 2 (a 1 Δ g , v = 0), a significantly different conclusion than that of the earlier study. We will show the results of Collins and Husain are consistent with the more direct experimental data presented here.…”
Section: ■ Introductionmentioning
confidence: 65%
“…In earlier work, Klais et al detected the a 1 Δ g ( v = 2,3) levels in a flash photolysis experiment and found them to disappear very quickly, although ozone interference prevented the detection of v = 1, which we know disappears even faster. They monitored the buildup of a 1 Δ g ( v = 0) and found it to be relatively slow after its initial appearance and unaffected by the addition of O 2 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The fact is that for such v' values in reaction (6), the energy transfer from the oxygen molecule to the nitrogen molecule has an almost resonant character. In both (5) and 6cases, it is obvious that a change in the reaction rate coefficient with a change in v is associated with a defect of the reaction energy (see Figure 4 where both experimental data [29,48,[50][51][52][53][54] and theoretical estimates [55] are presented). The smaller defect of energy, the greater the reaction rate coefficient.…”
Section: Energy Transfer In Collisional Reactionsmentioning
confidence: 99%
“…The values of the rate constants of the reactions of deexcitation of electronically-vibrationally excited O 2 molecules O 2 (a 1 g , v≥1) at collisions with N 2 are so small that such processes do not affect the populations of electronicvibrational levels under consideration in comparison with the processes of deexcitation at collisions with molecular oxygen. For estimations we used the maximum value for these rate constants 8.4×10 −14 cm 3 s −1 from Klais et al (1980), which is two orders of magnitude smaller than the rate constants of the processes of deexcitation at collisions with molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%